Coexistence of Cholangiocarcinoma and Poorly Differentiated Neuroendocrine Carcinoma in the Gallbladder: A Rare Case Report - Rahman, Bakrudeen Ali Habeeb; Shanthanaraj, Daniel; Rajendran, Deva Dharshini; Balaji, Prithiha; George, Keren Ann (Indian Journal of Pharmacy Practice)
Gallbladder cancer arising from the epithelial cells lining the bile ducts within gall bladder is known as cholangiocarcinoma of gall bladder. It is one of rarest and aggressive malignancies. This cancer is divided into different types depending on the location and histologic characteristics. Of these, high-grade neuroendocrine carcinoma is a very aggressive subtype. This rare subtype is much more high-grade and neuroendocrine than other neuroendocrine tumour, which comes with a quite unique set of challenges in terms of diagnosis and treatment. We report a case of an 83 years elderly female diagnosed as poorly differentiated neuroendocrine carcinoma of the gall bladder was presented to our department. The patient presentation is characterized by its severity and rapid progress, reflecting a common feature of this aggressive subtype. The rarity and high-grade nature of poorly differentiated neuroendocrine carcinoma complicate treatment and prognosis, highlighting the need for specialized medical attention and tailored therapeutic approaches. This case underscores the importance of considering this rare variant in the differential diagnosis of gall bladder malignancies, particularly in elderly patients presenting with advanced symptoms.
Keywords: Cholangiocarcinoma; Poorly differentiated neuroendocrine carcinoma; Mixed Adenoneuroendocrine carcinoma; Rare malignancy; Case report